5,7-Dimethoxycoumarin ameliorates vincristine induced neuropathic pain: potential role of 5HT3 receptors and monoamines - Usman, Muhammad; Malik, Hurmat; Tokhi, Ahmed; Arif, Mehreen; Huma, Zilli; Rauf, Khalid; Sewell, Robert D. E. (Frontiers in Pharmacology, 2023)
Vincristine is the drug of choice for Hodgkin's lymphoma, acute lymphoblastic leukemia, and non-Hodgkin lymphoma. Despite its significant anticancer effects, it causes dose-dependent neuropathy, leading to compulsive dose reduction. The available drugs used for vincristine-induced neuropathic pain (VINP) have a range of safety, efficacy, and tolerability issues prompting a search for new therapies. 5,7-Dimethoxycoumarin (5,7-DMC) also known as citropten, is a natural coumarin found in the essential oils of citrus plants such as lime, lemons, and bergamots, and it possesses both antidepressant and anti-inflammatory effects. This study was designed to investigate the possible analgesic and antiallodynic effects of 5,7-DMC in a murine model of VINP. Vincristine was administered to groups of BALB/c male mice (0.1 mg/kg intraperitoneally) once daily for 14 days to induce VINP. Thermal hyperalgesia and mechanical allodynia were quantified using the tail immersion test and von Frey filament application method. The levels of monoamine neurotransmitters and vitamin C in frontal cortical, striatal and hippocampal tissues, as well as the TNF-α level in plasma, were quantified using high performance liquid chromatography and ELISA respectively. On day 15 of the protocol, acute treatment with 5,7-DMC clearly reversed VINP thermal hyperalgesia, mechanical static allodynia, mechanical dynamic allodynia, and cold allodynia. The activity of 5,7-DMC against hyperalgesia and allodynia was inhibited by pretreatment with ondansetron but not naloxone, implicating a 5-HT3 receptor involvement. VINP vitamin C levels were restored by 5,7-DMC in the frontal cortex, and changes in serotonin, dopamine, adenosine, inosine and hypoxanthine levels caused by vincristine were reversed either fully or partially. Additionally, the vincristine-induced rise in hippocampal serotonin, dopamine, inosine and striatal serotonin was appreciably reversed by 5,7-DMC. 5,7-DMC also reversed the vincristine-induced increase in the plasma level of TNF-α. In negating the changes in the levels of some neurotransmitters in the brain caused by vincristine, 5,7-DMC showed stronger effects than gabapentin. It was concluded that, there is a potential role of 5-HT3 receptors and monoamines in the amelioration of VINP induced by 5,7-DMC, and the use of this compound warrants further investigation.